Light diffusing thermosetting sheet

By using a composition of thermosetting resin and surface-modified silica particles in the sealing material of the image display device, the problem of difficulty in achieving high haze value and full light transmittance in the prior art is solved, and excellent light diffusion and color impartment are achieved.

CN114730024BActive Publication Date: 2025-03-11MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080081525.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-23
Filing Date
2020-12-03
Publication Date
2025-03-11
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high haze values ​​and excellent all-light transmittance in the sealing material of the image display device, resulting in the optical element being susceptible to atmospheric moisture and deterioration.

Method used

The haze value and full light transmittance of the sealing layer are adjusted by adding an appropriate amount of surface-modified silica particles and pigment particles to the sealing layer.

Benefits of technology

It is achieved that the haze value of the sealing layer is increased without reducing the full light transmittance, thereby enhancing the light diffusivity and being able to impart a desired color to the sealing member.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114730024B_ABST
    Figure CN114730024B_ABST
Patent Text Reader

Abstract

The light diffusing thermosetting sheet contains a thermosetting resin composition including a thermosetting resin and surface-modified silica particles, and the surface-modified silica particles have an average primary particle size of 0.1 μm to 1.5 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a light diffusing thermosetting sheet. Background Art

[0002] Conventionally, it is known that an optical element included in an image display device is sealed with a sealing material in order to suppress degradation due to moisture in the atmosphere or the like.

[0003] As such a sealing material, for example, an image display device sealing material containing a biphenyl skeleton-containing epoxy resin and an alicyclic skeleton-containing epoxy resin has been proposed (for example, see Patent Document 1).

[0004] In addition, such an image display device sealing material seals the optical element by burying the optical element and then curing it.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2018 / 235824 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the use of the image display device sealing material described in Patent Document 1 for various applications is being studied, and it is desired to impart performance corresponding to each application to the image display device sealing material described in Patent Document 1.

[0010] For example, when the image display device sealing material described in Patent Document 1 is used for window glass of general buildings, window glass for vehicles, signs, lighting fixtures, lighting covers of display lamps, backlight diffusers for liquid crystals, display panels, etc., the following performance is required: the light emitted from the light source is diffused and transmitted with the same brightness, and the image of the light source such as the lamp is made invisible by reducing the straight-line transmitted light.

[0011] The present invention provides a light-diffusing thermosetting sheet that can achieve an improved haze value and a good appearance, and can impart excellent light diffusing properties to various products.

[0012] Means for solving problems

[0013] The present invention [1] comprises a light diffusing thermosetting sheet comprising a thermosetting resin composition comprising a thermosetting resin and surface-modified silica particles, wherein the average primary particle size of the surface-modified silica particles is 0.1 μm or more and 1.5 μm or less, and the surface-modified silica particles are silica particles surface-modified with a silane coupling agent.

[0014] The present invention [2] comprises the light diffusing thermosetting sheet described in the above [1], wherein the thermosetting resin comprises an epoxy resin.

[0015] The present invention [3] comprises the light diffusing thermosetting sheet described in [1] or [2] above, wherein the silica particles are non-porous.

[0016] The present invention [4] comprises the light diffusing thermosetting sheet according to any one of [1] to [3], wherein the content ratio of the surface modified silica particles is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the thermosetting resin.

[0017] The present invention [5] comprises the light-diffusing thermosetting sheet described in any one of [1] to [4] above, wherein, with respect to the thermosetting resin composition, when the thermosetting resin composition is formed into a sheet having a thickness of 15 μm and thermally cured, the haze value is 35% or more and the total light transmittance is 80% or more.

[0018] The present invention [6] comprises the light diffusing thermosetting sheet according to any one of [1] to [4], wherein the thermosetting resin composition further comprises pigment particles, and the average primary particle size of the pigment particles is 100 nm or less.

[0019] Effects of the Invention

[0020] According to the light diffusing thermosetting sheet of the present invention, since the thermosetting resin composition contains a thermosetting resin and surface-modified silica particles, the haze value of the cured product of the thermosetting resin composition can be improved, and the appearance can be improved. As a result, various products including the cured product of the thermosetting resin composition can be provided with excellent light diffusing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] [ Figure 1 ] Figure 1 This is a side cross-sectional view of a sealing sheet which is one embodiment of the light diffusing thermosetting sheet of the present invention.

[0022] [ Figure 2 ] Figure 2 As a Figure 1 The illustrated embodiment is a side cross-sectional view of an organic EL display with a touch sensor, which is one embodiment of an image display device (having an in-cell structure or an on-cell structure) in which a sealing member is formed of a sealing layer.

[0023] [ Figure 3 ] Figure 3This is a side cross-sectional view of an organic EL display with a touch sensor as another embodiment of the image display device (an embodiment having an out-cell structure). DETAILED DESCRIPTION

[0024] <Light-diffusing thermosetting sheet>

[0025] The light-diffusing thermosetting sealing sheet (hereinafter, also referred to as a sealing sheet) of the first embodiment of the light-diffusing thermosetting sheet of the present invention contains a thermosetting resin composition. The thermosetting resin composition contains a thermosetting resin and surface-modified silica particles.

[0026] <Thermosetting resin>

[0027] Examples of the thermosetting resin include epoxy resins, etc. In other words, the thermosetting resin includes, for example, epoxy resins, and is preferably composed of epoxy resins.

[0028] As the epoxy resin, for example, there can be mentioned bisphenol type epoxy resins (for example, bisphenol A type, bisphenol F type, bisphenol E type, bisphenol S type, bisphenol AD ​​type, and mixed types thereof, etc.), diphenyl ether type epoxy resins, Novolac type epoxy resins (for example, phenol Novolac type, cresol Novolac type, biphenyl Novolac type, bisphenol Novolac type, naphthol Novolac type, trisphenol Novolac type, dicyclopentadiene Novolac type, etc.), biphenyl type epoxy resins, naphthyl type epoxy resins, trisphenol alkane type epoxy resins (for example, trisphenol methane type, trisphenol ethane type, trisphenol propane type, etc.), epoxy resins containing an alicyclic skeleton, and the like.

[0029] The epoxy resins can be used alone or in combination of two or more.

[0030] Among the epoxy resins, preferably, a bisphenol epoxy resin, a biphenyl epoxy resin, and an epoxy resin containing an alicyclic skeleton are used, and more preferably, a bisphenol epoxy resin, a biphenyl epoxy resin, and an epoxy resin containing an alicyclic skeleton are used in combination.

[0031] In other words, the epoxy resin preferably includes at least one selected from the group consisting of bisphenol epoxy resin, biphenyl epoxy resin and epoxy resin containing an alicyclic skeleton, more preferably includes bisphenol epoxy resin, biphenyl epoxy resin and epoxy resin containing an alicyclic skeleton, and further preferably consists of bisphenol epoxy resin, biphenyl epoxy resin and epoxy resin containing an alicyclic skeleton.

[0032] When the epoxy resin includes a bisphenol epoxy resin, a biphenyl epoxy resin, and an epoxy resin containing an alicyclic skeleton, it is possible to reliably achieve an improvement in the total light transmittance of the sealing member described below.

[0033] The bisphenol epoxy resin may be solid at room temperature or liquid at room temperature, preferably solid at room temperature. It should be noted that the so-called "solid at room temperature" means a solid state without fluidity at room temperature (23°C), and the so-called "liquid at room temperature" means a liquid state with fluidity at room temperature (23°C) (the same applies hereinafter).

[0034] In other words, the bisphenol epoxy resin preferably includes a bisphenol epoxy resin that is solid at room temperature, and more preferably consists of a bisphenol epoxy resin that is solid at room temperature. When the bisphenol epoxy resin includes a bisphenol epoxy resin that is solid at room temperature, the sheet formability of the thermosetting resin composition can be improved, and the moisture permeability of the sealing component described later can be reduced.

[0035] Among such bisphenol-type epoxy resins, preferably, bisphenol F-type epoxy resin is used, and more preferably, bisphenol F-type epoxy resin which is solid at room temperature is used.

[0036] The weight average molecular weight (M) of bisphenol epoxy resin w ) is not particularly limited, and is, for example, 100 or more, preferably 1,000 or more, more preferably 5,000 or more, further preferably 10,000 or more, particularly preferably 20,000 or more, and particularly preferably 30,000 or more, and is, for example, 100,000 or less, and preferably 90,000 or less. Weight average molecular weight (M w ) can be determined by gel permeation chromatography (GPC) using polystyrene as a standard substance (the same applies hereinafter).

[0037] When the weight average molecular weight of the bisphenol epoxy resin is not less than the above lower limit, the barrier properties and flex resistance of the cured product of the thermosetting resin composition can be improved.

[0038] The epoxy equivalent of the bisphenol epoxy resin is, for example, 100 g / eq. or more, preferably 500 g / eq. or more, more preferably 2,000 g / eq. or more, further preferably 4,000 g / eq. or more, and particularly preferably 7,000 g / eq. or more, and is, for example, 20,000 g / eq. or less, and preferably 16,000 g / eq. or less. The epoxy equivalent can be measured in accordance with JIS K7236:2001 (hereinafter the same).

[0039] In the thermosetting resin, the content ratio of the bisphenol epoxy resin is, for example, 0 mass % or more, preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 20 mass % or more, for example, 100 mass % or less, preferably 70 mass % or less, more preferably 50 mass % or less.

[0040] The biphenyl type epoxy resin may be solid at room temperature or liquid at room temperature, and is preferably solid at room temperature.

[0041] In other words, the biphenyl type epoxy resin preferably includes a biphenyl type epoxy resin that is solid at room temperature, and more preferably consists of a biphenyl type epoxy resin that is solid at room temperature. When the biphenyl type epoxy resin includes a biphenyl type epoxy resin that is solid at room temperature, the sheet formability of the thermosetting resin composition can be reliably improved, and the moisture permeability of the sealing component described later can be reliably reduced.

[0042] The weight average molecular weight (M w ) is not particularly limited, and is, for example, 100 or more, preferably 1,000 or more, more preferably 5,000 or more, further preferably 10,000 or more, particularly preferably 20,000 or more, particularly preferably 30,000 or more, and is, for example, 100,000 or less, and preferably 90,000 or less.

[0043] When the weight average molecular weight of the biphenyl epoxy resin is not less than the above lower limit, the barrier properties and flex resistance of the cured product of the thermosetting resin composition can be improved.

[0044] The epoxy equivalent of the biphenyl type epoxy resin is, for example, 100 g / eq. or more, preferably 500 g / eq. or more, more preferably 2,000 g / eq. or more, further preferably 4,000 g / eq. or more, particularly preferably 7,000 g / eq. or more, and is, for example, 20,000 g / eq. or less, and preferably 16,000 g / eq. or less.

[0045] In the thermosetting resin, the content ratio of the biphenyl type epoxy resin is, for example, 0 mass % or more, preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 20 mass % or more, for example, 100 mass % or less, preferably 70 mass % or less, further preferably 50 mass % or less.

[0046] The epoxy resin containing an alicyclic skeleton is an epoxy resin having at least an epoxy group and an aliphatic ring (alicyclic skeleton).

[0047] The epoxy resin containing an alicyclic skeleton may be solid at room temperature or liquid at room temperature, preferably liquid at room temperature.

[0048] In other words, the epoxy resin containing an alicyclic skeleton preferably includes an epoxy resin containing an alicyclic skeleton that is liquid at room temperature, and more preferably consists of an epoxy resin containing an alicyclic skeleton that is liquid at room temperature. When the epoxy resin containing an alicyclic skeleton includes an epoxy resin containing an alicyclic skeleton that is liquid at room temperature, the transparency of the sealing component described later can be further improved, and the moisture permeability of the sealing component can be more reliably reduced.

[0049] Examples of the epoxy resin containing an alicyclic skeleton include alicyclic epoxy compounds having a cycloolefin oxide structure, dicyclopentadiene type epoxy resins (hereinafter referred to as DCPD type epoxy resins), hydrogenated epoxy resins, and the like.

[0050] Examples of the alicyclic epoxy compound having a cycloolefin oxide structure include an epoxy compound having an epoxycyclohexane structure (hereinafter referred to as an epoxy compound having an ECH structure) represented by the following formula (1), and modified products thereof.

[0051] Formula (1)

[0052] [Chemical formula 1]

[0053]

[0054] [In formula (1), X represents a single bond or a linking group (a divalent group having one or more atoms). A substituent such as an alkyl group may be bonded to the carbon atom constituting the cyclohexane ring, or may not be bonded.]

[0055] Examples of the linking group represented by X in the above formula (1) include a divalent hydrocarbon group, a carbonyl group, an ether group, a thioether group, an ester group, a carbonate group, an amide group, and a group formed by linking these groups.

[0056] Examples of the divalent hydrocarbon group include linear or branched alkylene groups having 1 to 18 carbon atoms (e.g., methylene, methylmethylene, dimethylmethylene, ethylene, propylene, trimethylene, etc.), cycloalkylene groups (e.g., 1,2-cyclopentylene, 1,3-cyclopentylene, 1,2-cyclohexylene, 1,3-cyclohexylene, 1,4-cyclohexylene, etc.), and cycloalkylidene groups (e.g., cyclopentylidene, cyclohexylidene, etc.).

[0057] Among the linking groups represented by X in the above formula (1), from the viewpoint of the adhesiveness of the sealing member described later, preferably, there are linking groups containing oxygen atoms, more preferably, there are carbonyl groups, ether groups, ester groups, and carbonate groups, and still more preferably, there are ester groups.

[0058] Examples of the epoxy compound containing an ECH structure represented by the above formula (1) include (3,3',4,4'-diepoxy)dicyclohexyl, bis(3,4-epoxycyclohexyl methyl) ether, 1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, 1,2-epoxy-1,2-bis(3,4-epoxycyclohexane-1-yl)ethane, 2,2-bis(3,4-epoxycyclohexane-1-yl)propane, 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate, and 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate modified with ε-caprolactone.

[0059] The epoxy compound having an ECH structure represented by the above formula (1) may be a commercially available product. Examples of the commercially available products include Celloxide 8000, Celloxide 2021P, and Celloxide 2081 manufactured by Daicel.

[0060] The dicyclopentadiene type epoxy resin (hereinafter referred to as DCPD type epoxy resin) is represented by the following formula (2).

[0061] [Chemical formula 2]

[0062]

[0063] [In formula (2), a substituent such as an alkyl group may or may not be bonded to the carbon atom constituting the aliphatic ring derived from dicyclopentadiene.]

[0064] The DCPD epoxy resin represented by the above formula (2) may also be a commercial product. Commercial products of the DCPD epoxy resin represented by the above formula (2) include, for example, EP-4088S (epoxy equivalent 170 g / eq.) manufactured by ADEKA Corporation and EP-4088L (epoxy equivalent 165 g / eq.) manufactured by ADEKA Corporation.

[0065] The hydrogenated epoxy resin is an epoxy resin obtained by hydrogenating an epoxy resin having an aromatic ring among the above-mentioned epoxy resins. Specific examples thereof include hydrogenated bisphenol epoxy resins and hydrogenated biphenyl epoxy resins, and preferably hydrogenated bisphenol epoxy resins are used.

[0066] Specific examples of the hydrogenated bisphenol epoxy resin include hydrogenated bisphenol F epoxy resin and hydrogenated bisphenol A epoxy resin.

[0067] A commercially available hydrogenated bisphenol epoxy resin may also be used.

[0068] Commercially available products of hydrogenated bisphenol F epoxy resins include, for example, YL-6753 manufactured by Mitsubishi Chemical Corporation. Commercially available products of hydrogenated bisphenol A epoxy resins include, for example, YX-8000 and YX-8034 manufactured by Mitsubishi Chemical Corporation, EXA-7015 manufactured by DIC Corporation, ST-3000 manufactured by Nippon Steel & Sumitomo Metal Chemicals, Rikaresin HBE-100 manufactured by New Nippon Chemicals, and EX-252 manufactured by Nagase Chemtex Corporation.

[0069] Such alicyclic skeleton-containing epoxy resins may be used alone or in combination of two or more.

[0070] Among the epoxy resins containing an alicyclic skeleton, preferably, there are hydrogenated epoxy resins and epoxy compounds containing an ECH structure.

[0071] In other words, the epoxy resin containing an alicyclic skeleton preferably includes a hydrogenated epoxy resin and / or an epoxy compound containing an ECH structure, more preferably includes a hydrogenated epoxy resin or an epoxy compound containing an ECH structure, and further preferably consists of a hydrogenated epoxy resin or an epoxy compound containing an ECH structure.

[0072] Among the hydrogenated epoxy resins, preferably, a hydrogenated bisphenol A type epoxy resin is used. Among the epoxy compounds containing an ECH structure, preferably, 3,4-epoxycyclohexylmethyl (3,4-epoxy)cyclohexanecarboxylate is used.

[0073] The weight average molecular weight of such an alicyclic skeleton-containing epoxy resin is, for example, 100 or more, preferably 180 or more, and for example, 1,000 or less, preferably 790 or less, and more preferably 500 or less.

[0074] The epoxy equivalent of the alicyclic skeleton-containing epoxy resin is, for example, 90 g / eq. or more, preferably 100 g / eq. or more, and for example, 300 g / eq. or less, preferably 200 g / eq. or less.

[0075] In the thermosetting resin, the content ratio of the epoxy resin containing an alicyclic skeleton is, for example, 0 mass % or more, preferably 10 mass % or more, more preferably 20 mass % or more, for example, 100 mass % or less, preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 35 mass % or less.

[0076] The content ratio of the thermosetting resin in the thermosetting resin composition is, for example, 60 mass % or more, preferably 70 mass % or more, for example, 95 mass % or less, preferably 92 mass % or less, more preferably 90 mass % or less.

[0077] <Surface modified silica particles>

[0078] The surface-modified silica particles are silica particles whose surfaces have been modified with a silane coupling agent.

[0079] The silica particles are preferably spherical. More preferably, the silica particles have a high degree of sphericity. The silica particles can be prepared, for example, by a dry method (combustion method or arc method).

[0080] The silica particles may be porous or non-porous. Compared with non-porous silica particles, porous silica particles have higher hygroscopicity and gas adsorption. Therefore, porous silica particles and non-porous silica particles are used differently depending on the purpose of the sealing sheet.

[0081] For example, when the sealing sheet is used as a sealing sheet for image display elements such as organic EL, the silica particles are preferably non-porous from the viewpoint of releasing components adsorbed to the silica particles.

[0082] It should be noted that the silica particles referred to herein are defined as porous silica particles having a specific surface area of ​​300 m 2 / g or more, and the specific surface area of ​​the non-porous silica particles is 30m 2 / g or less.

[0083] Examples of the silane coupling agent include epoxy group-containing silane coupling agents (e.g., γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.), amino group-containing silane coupling agents (e.g., N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyltriethoxysilane, 3-aminopropyltrimethoxysilane, etc.), and methacryl group-containing silane coupling agents (e.g., γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, etc.).

[0084] The silane coupling agents can be used alone or in combination of two or more.

[0085] Among the silane coupling agents, preferably, an epoxy group-containing silane coupling agent is used.

[0086] In order to prepare such surface-modified silica particles, the surface of the above-mentioned silica particles is treated with the above-mentioned silane coupling agent.

[0087] As a surface treatment method using a silane coupling agent, for example, the following method can be cited: a silane coupling agent is added to water to be hydrolyzed, and then a catalyst such as alcohol and acetic acid is added to dissolve the silane coupling agent in water to prepare an aqueous solution, and the silica particles are immersed in the aqueous solution to perform surface treatment. In addition, as a surface treatment method using a silane coupling agent, for example, the following method can also be cited: a treated powder formed of silica particles is contained in a treatment container, and the treated powder is stirred while reacting with the vaporized silane coupling agent.

[0088] The average primary particle size of the surface-modified silica particles is 0.1 μm or more, preferably 0.2 μm or more, more preferably 0.4 μm or more, and 1.5 μm or less, preferably 1.3 μm or less. The average primary particle size can be measured using a laser diffraction / scattering particle size distribution measuring device (HORIBA LA-750, etc.) (the same applies below). It should be noted that the average primary particle size in the present disclosure is the particle size corresponding to 50% of the volume accumulation from the small diameter side.

[0089] When the average primary particle size of the surface-modified silica particles is greater than or equal to the above lower limit, the haze value within the range of the present invention can be given to the sealing component described later. When the average primary particle size of the surface-modified silica particles is less than or equal to the above upper limit, the sedimentation of the surface-modified silica particles in the varnish of the thermosetting resin composition described later can be suppressed.

[0090] Commercially available surface-modified silica particles may be used. Examples of commercially available surface-modified silica particles include SE1050-SEO, SC-2050MB, and 10SE-CM1 manufactured by Admatechs.

[0091] The content ratio of the surface modified silica particles relative to 100 parts by mass of the thermosetting resin is, for example, 5 parts by mass or more, preferably 10 parts by mass or more, more preferably 20 parts by mass or more, for example, 50 parts by mass or less, preferably 40 parts by mass or less, more preferably 35 parts by mass or less.

[0092] The content ratio of the surface modified silica particles in the thermosetting resin composition is, for example, 3 mass % or more, preferably 4 mass % or more, more preferably 8 mass % or more, and for example, 40 mass % or less, preferably 30 mass % or less, more preferably 25 mass % or less.

[0093] When the content ratio of the surface-modified silica particles is above the above lower limit, the haze value of the sealing component described later can be reliably improved, and the light diffusivity of the sealing component can be improved. When the content ratio of the surface-modified silica particles is below the above upper limit, the total light transmittance of the sealing component described later can be reliably improved.

[0094] <Thermosetting agent>

[0095] The thermosetting resin composition preferably further contains a thermosetting agent.

[0096] Examples of the thermosetting agent include a thermal cationic curing agent and a thermal anionic curing agent that initiate a curing reaction of a thermosetting resin by heat.

[0097] The thermal cationic curing agent is a thermal acid generator that generates an acid (cation) by heating.

[0098] As the thermal cationic curing agent, a known thermal cationic polymerization initiator can be used. As the thermal cationic polymerization initiator, for example, AsF 6 - , SbF 6 - PF 6 - , BF 4 - , B(C 6 F 5 ) 4 - CF 3 SO 3 - As the counter anion, there can be used sulfonium salts, phosphonium salts, quaternary ammonium salts, diazonium salts, iodonium salts, and the like.

[0099] The thermal anionic curing agent is a basic compound that dissolves under the action of heat or a compound that becomes a basic compound by dissociation of bonds under the action of heat.

[0100] Examples of the thermal anionic curing agent include room temperature solid imidazole compounds, amine-epoxy adduct compounds (reaction products of amine compounds and epoxy compounds), and amine-isocyanate compounds (reaction products of amine compounds and isocyanate compounds).

[0101] The thermosetting agent can be used alone or in combination of two or more.

[0102] Among the heat curing agents, preferably, a heat cationic curing agent is used, and more preferably, a quaternary ammonium salt is used.

[0103] The content ratio of the thermosetting agent relative to 100 parts by mass of the thermosetting resin is, for example, 0.3 parts by mass or more, preferably 0.5 parts by mass or more, for example, 10 parts by mass or less, preferably 5 parts by mass or less.

[0104] The content ratio of the thermosetting agent in the thermosetting resin composition is, for example, 1 mass % or more, preferably 2 mass % or more, and for example, 10 mass % or less, preferably 5 mass % or less.

[0105] <Pigment>

[0106] In addition, depending on the use of the sealing member described below, it may be desirable to impart a desired color to the sealing member. In this case, the thermosetting resin composition preferably contains pigment particles.

[0107] When the thermosetting resin composition contains surface-modified silica particles and pigment particles, a desired color can be imparted to the sealing member described below, and the haze value and the total light transmittance can be adjusted in a well-balanced manner.

[0108] The pigment particles are solvent-dispersible pigments that can be dispersed in a solvent and have a particle shape.

[0109] The average primary particle size of the pigment particles is, for example, 10 nm or more, preferably 30 nm or more, and for example, 100 nm or less, preferably 70 nm or less.

[0110] When the average primary particle size of the pigment particles is greater than or equal to the above lower limit, the content of the pigment particles described below can be reduced. When the average primary particle size of the pigment particles is less than or equal to the above upper limit, transparency can be ensured in the sealing member described below.

[0111] Examples of the pigment particles include inorganic pigment particles, more specifically black pigment particles such as carbon black, oxide pigments, hydroxide pigments, etc. The pigment particles may be used alone or in combination of two or more.

[0112] Among the pigment particles, preferably, inorganic pigment particles are used, more preferably, black pigment particles are used, and further preferably, carbon black is used.

[0113] The content ratio of the pigment particles relative to 100 parts by mass of the thermosetting resin is, for example, 0.01 parts by mass or more, preferably 0.1 parts by mass or more, for example, 10 parts by mass or less, preferably 5 parts by mass or less, and more preferably 2 parts by mass or less.

[0114] The content ratio of the pigment particles in the thermosetting resin composition is, for example, 0.1 mass % or more, preferably 0.2 mass % or more, and for example, 15 mass % or less, preferably 10 mass % or less, and more preferably 5 mass % or less.

[0115] When the content of the pigment particles is greater than or equal to the lower limit, the sealing member described below can be given a desired color. When the content of the pigment particles is less than or equal to the upper limit, the sealing member described below can be given a desired color while fully ensuring total light transmittance.

[0116] <Other ingredients>

[0117] The thermosetting resin composition may contain other ingredients other than the above in appropriate proportions as required. Other ingredients include thermoplastic resins, coupling agents, leveling agents, polymerization initiation aids, anti-aging agents, wettability improvers, surfactants, plasticizers, ultraviolet absorbers, preservatives, antibacterial agents, etc.

[0118] <Light-diffusing thermosetting sheet>

[0119] Next, refer to Figure 1 Next, a sealing sheet 1 which is one embodiment of the light diffusing thermosetting sheet of the present invention will be described.

[0120] like Figure 1 As shown, the sealing sheet 1 includes a sealing layer 2 formed of the above-mentioned thermosetting resin composition, a base film 3 , and a release film 4 .

[0121] In order to prevent foreign matter from adhering to the sealing layer 2, etc., the sealing layer 2 is preferably protected by the base film 3 and the release film 4 when the sealing sheet 1 is stored. In addition, when the sealing sheet 1 is used, the base film 3 and the release film 4 are peeled off.

[0122] The sealing layer 2 is a dried product of the thermosetting resin composition and has a sheet shape (flat plate shape). Specifically, the sealing layer 2 has a predetermined thickness, extends in a predetermined direction perpendicular to the thickness direction, and has a flat surface and a flat back surface.

[0123] In the sealing layer 2 , the above-mentioned thermosetting resin is not reacted (cured), and the sealing layer 2 contains the thermosetting resin in an uncured state.

[0124] The thickness of the sealing layer 2 is, for example, 1 μm or more, preferably 5 μm or more, and for example, 100 μm or less, preferably 30 μm or less.

[0125] In addition, when the sealing layer 2 having a thickness of 15 μm is cured (i.e., when the thermosetting resin composition is formed into a sheet having a thickness of 15 μm and thermally cured), the haze value of the cured product of the sealing layer 2 is, for example, 30% or more, preferably 35% or more, more preferably 40% or more, particularly preferably 50% or more, particularly preferably 80% or more, for example, 100% or less, preferably 95% or less. It should be noted that the haze value can be measured by the method described in the Examples described later.

[0126] When the haze value of the cured product of the sealant layer 2 is greater than the lower limit, the sealant layer can be thickened without significantly increasing the haze value. When the haze value of the cured product of the sealant layer 2 is less than the upper limit, the sealant layer can be thinned without significantly decreasing the haze value.

[0127] In addition, when the sealing layer 2 having a thickness of 15 μm is cured, the total light transmittance of the cured product of the sealing layer 2 is, for example, 10% or more, preferably 20% or more, more preferably 50% or more, further preferably 70% or more, particularly preferably 80% or more, particularly preferably 85% or more, and most preferably 90% or more, for example, 100% or less, preferably 98% or less. It should be noted that the total light transmittance can be measured by the method described in the Examples below.

[0128] When the total light transmittance of the cured product of the sealing layer 2 is equal to or greater than the above lower limit, light extraction loss can be reduced. When the total light transmittance of the cured product of the sealing layer 2 is equal to or less than the above upper limit, light extraction loss can be eliminated.

[0129] When the haze value of the cured product of the sealing layer 2 is equal to or greater than the above lower limit and the total light transmittance is equal to or greater than the above lower limit, the light diffusibility of the cured product of the sealing layer 2 can be reliably improved.

[0130] In order to support and protect the sealing layer 2 until the sealing sheet 1 is used to form a sealing component, the base film 3 is attached to the back of the sealing layer 2 in a peelable manner. That is, the base film 3 is a flexible film that is laminated on the back of the sealing layer 2 in a manner of covering the back of the sealing layer 2 during shipment, transportation, and storage of the sealing sheet 1, and can be peeled off from the back of the sealing layer 2 in a manner bent into a substantially U-shape just before the sealing sheet 1 is used.

[0131] The base film 3 has a flat plate shape, specifically, has a predetermined thickness, extends in a predetermined direction perpendicular to the thickness direction, and has a flat front surface and a flat back surface. The adhesive surface (front surface) of the base film 3 is subjected to a peeling treatment as needed.

[0132] Examples of the material of the base film 3 include resin materials such as polyester (for example, polyethylene terephthalate (PET)), polyolefin (for example, polyethylene, polypropylene, etc.).

[0133] The base film 3 preferably has a moisture barrier or gas barrier property, and more preferably a film made of polyethylene terephthalate. The thickness of the base film 3 is appropriately selected according to the material of the film, but can be, for example, 25 μm to 150 μm in order to conform to the sealed material such as the display element.

[0134] During the period until the sealing sheet 1 is used for forming the sealing component, the release film 4 is attached to the surface of the sealing layer 2 in a removable manner in order to protect the sealing layer 2. That is, the release film 4 is a flexible film that is laminated on the surface of the sealing layer 2 in a manner covering the surface of the sealing layer 2 during shipment, transportation, and storage of the sealing sheet 1, and can be peeled off from the surface of the sealing layer 2 in a manner bent into a substantially U-shape just before the sealing sheet 1 is used.

[0135] The release film 4 has a flat plate shape, specifically, has a predetermined thickness, extends in a predetermined direction orthogonal to the thickness direction, and has a flat surface and a flat back surface. In addition, the adhesive surface (back surface) of the release film 4 is peeled off as required. As the material of the release film 4, for example, the same resin material as the base film 3 can be cited. Although the thickness of the release film 4 is also appropriately selected according to the material of the film, it can be, for example, 25 μm or more and 150 μm or less from the aspect of having the ability to follow the sealed material such as the display element.

[0136] <Method for producing sealing sheet>

[0137] Next, the manufacturing method of the sealing sheet 1 is demonstrated.

[0138] In order to manufacture the sealing sheet 1, first, the above-mentioned thermosetting resin composition is prepared.

[0139] The thermosetting resin composition is prepared by mixing the thermosetting resin, the surface-modified silica particles, the thermosetting agent added as needed, the pigment particles, and the other components. In the manufacture of the sealing sheet 1, the thermosetting resin composition is preferably diluted with an organic solvent to prepare a varnish of the thermosetting resin composition.

[0140] As long as the organic solvent can evenly disperse or dissolve the thermosetting resin and the surface-modified silica particles, there is no particular limitation. As the organic solvent, for example, aromatic hydrocarbons (for example, benzene, toluene, xylene, etc.), ketones (for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), ethers (for example, dibutyl ether, tetrahydrofuran, dioxane, ethylene glycol monoalkyl ether, ethylene glycol dialkyl ether, 1-methoxy-2-propanol, etc.), esters (for example, ethyl acetate, butyl acetate, 2-methoxymethyl ethyl acetate, etc.), nitrogen-containing compounds (for example, N-methylpyrrolidone, dimethylimidazolidinone, dimethylformaldehyde, etc.), etc. can be cited. The organic solvent can be used alone or in combination of two or more.

[0141] Among the organic solvents, preferably, ketones are used, and more preferably, methyl ethyl ketone is used.

[0142] The content ratio of the organic solvent relative to 100 parts by mass of the thermosetting resin composition is, for example, 50 parts by mass or more, preferably 80 parts by mass or more, for example, 200 parts by mass or less, preferably 150 parts by mass or less.

[0143] In addition, as a mixing method for the above-mentioned components (thermosetting resin, surface-modified silica particles, thermosetting agent, pigment particles, other components and organic solvent), for example, dispersion mixing using a ball mill, stirring in a flask, kneading using a three-roll mill, etc. can be cited.

[0144] In addition, the above components may be mixed together, or a part of the above components may be dispersed or dissolved in the above organic solvent in advance, and the dispersion or solution thereof may be mixed with the remaining components. For example, the surface-modified silica particles may be uniformly dispersed in an organic solvent in advance using ultrasound or the like, and then the dispersion thereof may be mixed with the remaining components (thermosetting resin, etc.). In addition, the pigment particles may be uniformly dispersed in an organic solvent (preferably an ester) in advance, and then the dispersion thereof may be mixed with the remaining components (thermosetting resin, etc.).

[0145] Next, a thermosetting resin composition is applied to the surface of the base film 3 by a known method.

[0146] Examples of a method for applying the thermosetting resin composition include screen printing, a dispenser, and a coating roll.

[0147] Next, the thermosetting resin composition is dried, and the organic solvent is volatilized as necessary, thereby forming a coating film.

[0148] The heating temperature is a temperature at which the thermosetting resin dries without curing, and is, for example, 20° C. or more, preferably 90° C. or more, for example, 120° C. or less, preferably less than 100° C. The heating time is, for example, 1 minute or more, preferably 2 minutes or more, for example, 30 minutes or less, preferably 15 minutes or less.

[0149] Thereby, the coating film is dried, and the sealing layer 2 formed of the thermosetting resin composition is prepared. Next, the release film 4 is attached to the surface of the sealing layer 2 .

[0150] In the above manner, the sealing sheet 1 is manufactured.

[0151] Such a sealing sheet 1 can be applied to applications requiring light diffusion, such as image display devices, lighting covers, window glass, etc. When the sealing sheet 1 is applied to various applications, after a sealed material (e.g., a light source, etc.) is embedded in the sealing layer 2, the sealing layer 2 is heated, for example, at 80° C. to 120° C. for 0.5 to 3 hours to cure.

[0152] <Manufacturing of image display device>

[0153] The sealing sheet 1 can be suitably used, for example, for sealing a light source (display element, optical element) of an image display device. Figure 2 , an organic EL display with a touch sensor (hereinafter referred to as an organic EL display 10 ) as one embodiment of an image display device will be described.

[0154] It should be noted that, in this embodiment, an organic EL display with a touch sensor is cited as an image display device, but the image display device is not particularly limited. As an image display device, for example, a liquid crystal display (including a liquid crystal display with a touch sensor), an organic EL display (including an organic EL display with a touch sensor), a Micro LED display, etc. can be cited.

[0155] The organic EL display 10 includes a device mounting unit 11 , a sealing member 14 , and a cover glass or a barrier film 15 .

[0156] The element mounting unit 11 includes a substrate 13 , an organic EL element 12 , a barrier layer 16 , and electrodes (not shown).

[0157] The substrate 13 supports the organic EL element 12. The substrate 13 preferably has flexibility.

[0158] The organic EL element 12 is a known organic EL element, and is mounted on a substrate 13. Although not shown, the organic EL element 12 includes a cathode reflective electrode, an organic EL layer, and an anode transparent electrode.

[0159] The barrier layer 16 covers the organic EL element 12 to prevent moisture in the atmosphere from coming into contact with the organic EL element 12. The barrier layer 16 includes a first inorganic barrier layer 17, a planarizing layer 19, and a second inorganic barrier layer 18.

[0160] The first inorganic barrier layer 17 is arranged on the upper surface and the side surface of the organic EL element 12 in a manner of surrounding the organic EL element 12. As the material of the first inorganic barrier layer 17, for example, metal oxides (for example, aluminum oxide, silicon oxide, copper oxide, etc.), metal nitrides (for example, aluminum nitride, silicon nitride, etc.), etc. can be cited. The material of the first inorganic barrier layer 17 can be used alone or in combination of two or more. Among the materials of the first inorganic barrier layer 17, metal nitrides can be preferably cited, and silicon nitride can be more preferably cited.

[0161] The planarization layer 19 is disposed on the upper surface of the first inorganic barrier layer 17. Examples of the material of the planarization layer 19 include known resin materials.

[0162] The second inorganic barrier layer 18 is disposed on the upper surface and side surfaces of the planarizing layer 19 so as to surround the planarizing layer 19. Examples of the material of the second inorganic barrier layer 18 include the same materials as those of the first inorganic barrier layer 17.

[0163] The electrode (not shown) constitutes a sensor of the organic EL display with a touch sensor. The electrode (not shown) is located between the substrate 13 and the sealing member 14. For example, the electrode (not shown) may be located inside the substrate 13 or on the organic EL element 12.

[0164] The sealing member 14 is a cured product of the sealing layer 2 (sealing sheet), and seals the organic EL element 12 covered by the barrier layer 16. The sealing member 14 is formed by the sealing layer 2 from which the base film 3 and the release film 4 are peeled off. Specifically, the sealing layer 2 from which the base film 3 and the release film 4 are peeled off is pasted on the substrate 13 in a manner that the organic EL element 12 covered by the barrier layer 16 is buried, and then a glass cover plate or a barrier film 15 is pasted on the upper surface of the sealing layer 2, and then the sealing layer 2 is cured. Thus, the sealing member 14 is formed.

[0165] The moisture permeability of the sealing member 14 is, for example, 20 g / m 2 · More than 24h, for example less than 45g / m 2 · 24h. It should be noted that the moisture permeability can be measured according to the method described in the examples below.

[0166] When the water vapor permeability of the sealing member 14 is equal to or less than the above upper limit, degradation of the optical element sealed by the sealing member 14 can be suppressed.

[0167] The glass cover or barrier film 15 is disposed on the upper surface of the sealing member 14. Although not shown, the glass cover or barrier film 15 includes a glass plate and electrodes provided on the lower surface of the glass plate, and constitutes a sensor of the organic EL display with a touch sensor.

[0168] Such an organic EL display 10 has an in-cell structure in which the organic EL element 12 is disposed between two electrodes constituting a sensor, or an on-cell structure in which one of the two electrodes constituting a sensor is disposed on the organic EL element 12 .

[0169] <Effects>

[0170] In the light diffusing thermosetting sheet, the thermosetting resin composition contains a thermosetting resin. Therefore, the thermosetting resin composition can seal the material to be sealed (for example, a light source) by curing after burying the material to be sealed.

[0171] However, if a large amount of filler is added to a thermosetting resin such as epoxy resin, although the haze value can generally be increased and the light diffusion property is improved, the total light transmittance tends to decrease. Therefore, it is difficult to simultaneously achieve an increase in the haze value and an excellent total light transmittance.

[0172] In addition, fillers are usually easy to aggregate in organic solvents and have poor dispersibility in thermosetting resins such as epoxy resins. Therefore, when a varnish of a thermosetting resin composition containing a large amount of fillers is applied, the following problems may occur: the surface of the coating film becomes rough due to the aggregated fillers; and the filler concentration becomes uneven.

[0173] In contrast, in the above-mentioned light-diffusing thermosetting sheet, the thermosetting resin composition contains surface-modified silica particles. Therefore, for the cured product of the thermosetting resin composition, the haze value can be improved and excellent total light transmittance can be ensured. As a result, the cured product of the thermosetting resin composition can simultaneously achieve a sufficient haze value and excellent total light transmittance, and can ensure excellent light diffusivity.

[0174] In addition, in the case of surface-modified silica particles, the surface of the silica particles is modified by a silane coupling agent, so that the adhesion between the surface-modified silica particles and the thermosetting resin can be improved, and during the long-term storage of the thermosetting resin composition (especially the varnish of the thermosetting resin composition), the sedimentation of the surface-modified silica particles can be suppressed, and the storage characteristics of the thermosetting resin composition can be improved. It is believed that the reason is that the presence of the silane coupling agent on the surface of the silica particles prevents the surface-modified silica particles from agglomerating with each other.

[0175] In addition, depending on the purpose of the sealing component, it is sometimes desired to give the sealing component a desired color and light diffusibility. In this case, the thermosetting resin composition preferably contains pigment particles in addition to the surface-modified silica particles. When the thermosetting resin composition contains surface-modified silica particles and pigment particles, the sealing component can be given a desired color, and the haze value and total light transmittance of the sealing component can be adjusted in a well-balanced manner, and light diffusibility can be ensured.

[0176] <Modification>

[0177] In the modification, the same components and steps as those in the above-described embodiment are denoted by the same reference numerals, and detailed description thereof is omitted.

[0178] like Figure 1 As shown, the sealing sheet 1 includes a sealing layer 2, a base film 3, and a release film 4, but the sealing sheet is not limited thereto. The sealing sheet only needs to include the sealing layer 2, and may not include the base film 3 and / or the release film 4. That is, the sealing sheet may be composed of only the sealing layer 2, or may include any one of the base film 3 and the release film 4, and the sealing layer 2.

[0179] like Figure 2 As shown in the figure, the organic EL display 10 includes the barrier layer 16 , but the present invention is not limited thereto. The organic EL display 10 may not include the barrier layer 16 .

[0180] The organic EL display 10 has an in-cell structure in which the organic EL element 12 is disposed between two electrodes constituting a sensor, or an on-cell structure in which one of the two electrodes is disposed on the organic EL element 12, but is not limited thereto.

[0181] For example, Figure 3 As shown, the organic EL display 20 may have an out-cell structure, that is, two electrodes constituting a sensor are arranged above the sealing member 14. The organic EL display 20 includes the above-mentioned element mounting unit 11, the above-mentioned sealing member 14, and a sensor unit 25.

[0182] The sensor unit 25 is disposed on the sealing member 14. The sensor unit 25 includes electrodes constituting sensors of the organic EL display with a touch sensor. In addition, in the organic EL display 20, the substrate 13 does not include electrodes.

[0183] in addition, Figure 2 and Figure 3 In the embodiment, the sealing member 14 seals the organic EL element 12 covered with the barrier layer 16, but the sealing member 14 may be provided at another position.

[0184] In addition, in the above-mentioned embodiment, the sealing sheet 1 is thermally cured when or after contacting the sealed material, thereby sealing the sealed material, but the light diffusing thermosetting sheet of the present invention is not limited to the sealing material. For example, the light diffusing thermosetting sheet may be thermally cured in advance, and then the cured product of the light diffusing thermosetting sheet may be attached to the object to be imparted with light diffusivity using other adhesives and / or other bonding agents.

[0185] The above-mentioned respective modifications also achieve the same effects as those of the above-mentioned embodiment. The above-mentioned embodiment and modifications may be combined as appropriate.

[0186] Example

[0187] The following examples and comparative examples are shown to explain the present invention in more detail, but the present invention is not limited to these. The specific numerical values ​​such as the mixing ratio (containing ratio), physical property values, and parameters used in the following description can be replaced by the upper limit value (defined as "below", "lower than") or lower limit value (defined as "above", "exceeding") of the mixing ratio (containing ratio), physical property values, and parameters corresponding to these described in the above-mentioned "Specific Implementation Methods". It should be noted that, unless otherwise specified, "parts" and "%" are based on mass.

[0188] <Raw materials>

[0189] The raw materials used in Examples and Comparative Examples are shown below.

[0190] Alicyclic skeleton-containing epoxy resin A: (3,4-epoxy)cyclohexanecarboxylic acid 3,4-epoxycyclohexylmethyl ester, molecular weight 252.3, epoxy equivalent 128-145 g / eq., trade name Celloxide 2021P (CEL2021P), manufactured by Daicel Corporation;

[0191] Alicyclic skeleton-containing epoxy resin B: hydrogenated bisphenol A type epoxy resin, weight average molecular weight 352, epoxy equivalent 205 g / eq., trade name YX8000, manufactured by Mitsubishi Chemical Corporation;

[0192] Alicyclic skeleton-containing epoxy resin C: DCPD type epoxy resin, weight average molecular weight 340, epoxy equivalent 165 g / eq., trade name EP-4088L, manufactured by ADEKA Corporation;

[0193] Bisphenol F type liquid epoxy resin A: Bisphenol F type epoxy resin in liquid state at room temperature, weight average molecular weight 398, epoxy equivalent 165 g / eq., trade name YL983U, manufactured by Mitsubishi Chemical Corporation;

[0194] Bisphenol F type solid epoxy resin B: bisphenol F type epoxy resin solid at room temperature, weight average molecular weight 7582, epoxy equivalent 10,000 g / eq., trade name jER4005P, manufactured by Mitsubishi Chemical Corporation;

[0195] Bisphenol mixed solid epoxy resin C: Bisphenol A / bisphenol F type solid epoxy resin solid at room temperature, weight average molecular weight 58,287, epoxy equivalent 8,400 g / eq., trade name jER4275, manufactured by Mitsubishi Chemical Corporation;

[0196] Biphenyl epoxy resin A: biphenyl epoxy resin solid at room temperature, weight average molecular weight 36,691, epoxy equivalent 10,000 g / eq., trade name XY-6954B35, manufactured by Mitsubishi Chemical Corporation;

[0197] Methyl ethyl ketone (MEK) solution of biphenyl epoxy resin A: prepared by dissolving biphenyl epoxy resin A in MEK. The concentration of biphenyl epoxy resin A is 35% by mass;

[0198] Non-porous surface-modified spherical silica particles A: average primary particle size 0.3 μm, treated with a silane coupling agent containing an epoxy group, trade name SE1050-SEO, manufactured by Admatechs;

[0199] Non-porous surface-modified spherical silica particles B: average primary particle size 0.5 μm, treated with an epoxy-containing silane coupling agent, trade name SC-2050MB, manufactured by Admatechs, slurry product (containing 30% by mass of MEK);

[0200] Non-porous surface-modified spherical silica particles C: average primary particle size 1.3 μm, treated with an epoxy-containing silane coupling agent, trade name 10SE-CM1, manufactured by Admatechs, slurry product (containing 25% by mass of MEK);

[0201] MEK dispersion of non-porous surface-modified spherical silica particles A: The non-porous surface-modified spherical silica particles A were dispersed in MEK for 30 minutes using ultrasound. The concentration of the non-porous surface-modified spherical silica particles was 60% by mass;

[0202] Porous spherical silica particles D: average primary particle size of 1.0 μm, no surface modification, trade name Hipresica FQ, manufactured by Ube-exsymo Co., Ltd.;

[0203] MEK dispersion of porous spherical silica particles D: prepared by dispersing porous spherical silica particles D in MEK using ultrasonic waves for 30 minutes. The concentration of the porous spherical silica particles is 60% by mass;

[0204] Silicone resin powder spherical particles A: average primary particle size 2.0 μm, trade name KMP-590, manufactured by Shin-Etsu Silicone Co., Ltd.;

[0205] MEK dispersion of silicone resin powder spherical particles A: Prepared by dispersing silicone resin powder spherical particles A in MEK using ultrasound for 30 minutes. The concentration of silicone resin powder spherical particles is 60% by mass;

[0206] Silicone rubber composite powder spherical particles B: average primary particle size 2.0 μm, trade name KMP-605, manufactured by Shin-Etsu Silicone Co., Ltd.;

[0207] MEK dispersion of silicone rubber composite powder spherical particles B: prepared by dispersing silicone rubber composite powder spherical particles B in MEK using ultrasound for 30 minutes. The concentration of silicone rubber composite powder spherical particles is 60% by mass;

[0208] Pigment particle dispersion: a solvent-based carbon black dispersion obtained by dispersing pigment particles (carbon black, average primary particle size 50 nm) in a mixed solvent of 2-methoxymethylethyl acetate / ethyl acetate / butyl acetate, with a pigment concentration of 12% by mass, trade name TSBK-105, manufactured by Daisei Chemical Co., Ltd.;

[0209] Thermal cationic curing agent: trade name CXC-1612, manufactured by King Industries;

[0210] Thermal anionic curing agent: 2-ethyl-4-methylimidazole, trade name 2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.

[0211] Coupling agent: trade name KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.

[0212] Organic solvent: methyl ethyl ketone (MEK)

[0213] <Example 1>

[0214] The epoxy resin B containing an alicyclic skeleton, bisphenol F type solid epoxy resin B, MEK solution of biphenyl type epoxy resin A, non-porous surface modified spherical silica particles A, thermal cationic curing agent, coupling agent, and organic solvent were mixed in the formula shown in Table 1 to prepare a varnish of a thermosetting resin composition.

[0215] Next, the varnish was applied on a PET film (a release-treated PET film (trade name: Purex A53, manufactured by Teijin Dupont Film Co., Ltd., thickness: 38 μm, base film)) using a coater, and then dried at 90° C. for 3 minutes in a nitrogen-purged oven to form a sealing layer with a thickness of 15 μm.

[0216] Next, a PET film (a release-treated PET film (trade name: Purex A31, manufactured by Teijin Dupont Film Co., Ltd., thickness: 38 μm, release film)) was laminated onto the sealant layer at 80°C using a heat laminator.

[0217] In the above manner, a sealing sheet including a sealing layer, a base film, and a release film was prepared.

[0218] <Examples 2 to 10, Comparative Examples 1 to 6>

[0219] Except having changed the formulation of each raw material into the formulation shown in Table 1 and Table 2, it carried out similarly to Example 1, and prepared the varnish and sealing sheet of the thermosetting resin composition.

[0220] <Example 11>

[0221] An epoxy resin B containing an alicyclic skeleton, a bisphenol F type solid epoxy resin B, a MEK solution of a biphenyl type epoxy resin A, a dispersion of pigment particles, non-porous surface-modified spherical silica particles B, a thermal cationic curing agent, and a coupling agent were mixed in the formula shown in Table 3 to prepare a varnish of a thermosetting resin composition.

[0222] Next, the varnish was applied on a PET film (a release-treated PET film (trade name: Purex A53, manufactured by Teijin Dupont Film Co., Ltd., thickness: 38 μm, base film)) using a coater in such a manner as to have a coating film thickness shown in Table 3, and then dried at 90° C. for 3 minutes in a nitrogen-purged oven to form a sealing layer.

[0223] Next, a PET film (a release-treated PET film (trade name: Purex A31, manufactured by Teijin Dupont Film Co., Ltd., thickness: 38 μm, release film)) was laminated onto the sealant layer at 80°C using a heat laminator.

[0224] In the above manner, a sealing sheet including a sealing layer, a base film, and a release film was prepared.

[0225] <Examples 12 to 18, Comparative Examples 7 and 8>

[0226] Except having changed the formulation of each raw material into the formulation shown in Table 3, it carried out similarly to Example 11, and prepared the varnish and sealing sheet of the thermosetting resin composition.

[0227] <Evaluation>

[0228] [Particle Sedimentation]

[0229] 30 g of the varnish prepared in each of the examples and comparative examples shown in Table 1 and Table 2 was placed in a 50 ml spiral tube (35 mm in diameter) and allowed to stand at room temperature (23° C.) for 24 hours. The presence or absence of sediment was then visually confirmed. The particle sedimentation properties were then evaluated according to the following criteria. The results are shown in Table 1 and Table 2.

[0230] No sediment: ○

[0231] There is sediment: ×

[0232] [90° peel strength]

[0233] Prepare an aluminum-PET composite film (aluminum surface) / resin / alkali glass spring balance (for weighing 1 kg). After peeling off the release film of the sealing sheet of each embodiment and each comparative example shown in Table 1 and Table 2 from the sealing layer, stick the sealing layer on the aluminum surface of the aluminum-PET composite film. Then, cure the sealing layer at 100°C for 1 hour. (In Examples 9, 10 and Comparative Example 3, cure at 100°C for 2 hours.)

[0234] Next, the 90-degree peel strength between the aluminum surface and the cured product of the sealant layer was measured. In Examples 1 to 10 and Comparative Examples 1 to 6, the 90-degree peel strength was used as the adhesive strength. The results are shown in Tables 1 and 2.

[0235] [Moisture Permeability]

[0236] After the release film of the sealing sheet of each Example and each Comparative Example shown in Table 1 and Table 2 was peeled off from the sealing layer, the sealing layer was cured at 100° C. for 1 hour. (In Examples 9 and 10 and Comparative Example 3, the curing was performed at 100° C. for 2 hours.)

[0237] Next, the base film was peeled off from the cured sealing layer to obtain a sample for measurement. The moisture permeability (moisture permeability) of the obtained sample was measured under the conditions of 60°C and 90%RH according to JIS Z0208. Then, the film thickness of the sample used in the measurement was converted to the value when the thickness of the sample was 100 μm. The results are shown in Tables 1 and 2.

[0238] [Haze value, total light transmittance (TT)]

[0239] After the release film of the sealing sheet of each Example and each Comparative Example shown in Table 1 to Table 3 was peeled off from the sealing layer, the sealing layer was cured at 100° C. for 1 hour. (In Examples 9 and 10 and Comparative Example 3, the curing was performed at 100° C. for 2 hours.)

[0240] Next, the base film is peeled off from the cured sealing layer to obtain a sample for measurement. The haze value and total light transmittance of the obtained sample are measured using a haze meter NDH2000 manufactured by Nippon Denshoku Industries. The results are shown in Tables 1 to 3. In particular, it was confirmed that excellent light diffusion is achieved by simultaneously achieving a haze value of more than 80% and a total light transmittance of more than 90%. In addition, it was confirmed that by adding pigment particles to the thermosetting resin composition, the desired color can be given to the cured product of the sealing layer, and the haze value and total light transmittance can be adjusted in a well-balanced manner in the cured product of the sealing layer.

[0241] [Appearance of the sealing layer]

[0242] After the release film of the sealing sheet of each Example and each Comparative Example shown in Table 1 to Table 3 was peeled off from the sealing layer, the sealing layer was cured at 100° C. for 1 hour. (In Examples 9 and 10 and Comparative Example 3, the curing was performed at 100° C. for 2 hours.)

[0243] The cured sealing layer was visually observed, and a smooth surface was evaluated as ○, and a rough surface was evaluated as ×. The results are shown in Tables 1 to 3.

[0244] [L * Value (blackness)]

[0245] After peeling the release film of the sealing sheet of each Example and each Comparative Example shown in Table 3 from the sealing layer, the sealing layer was cured at 100° C. for 1 hour.

[0246] Next, the base film was peeled off from the cured sealant layer to obtain a sample for measurement. The L * The results are shown in Table 3.

[0247] [Table 1]

[0248]

[0249] [Table 2]

[0250]

[0251] [Table 3]

[0252]

[0253] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but it is only an example and is not to be construed as limiting. Modifications of the present invention known to those skilled in the art are also included in the claims.

[0254] Industrial Applicability

[0255] The light-diffusing thermosetting sheet of the present invention can be applied to, for example: window glass of general buildings; window glass for vehicles; light-transmitting covering materials (glazing materials); protective covers for signs, lighting fixtures, display lights, etc.; image display devices (organic EL displays, liquid crystal displays, Micro LED displays, etc.).

Claims

1. A light-diffusing thermosetting sheet, characterized in that: The invention discloses a thermosetting resin composition comprising a thermosetting resin and surface-modified silica particles, wherein the surface-modified silica particles have an average primary particle size of 0.1 μm or more and 1.5 μm or less, and the surface-modified silica particles are silica particles surface-modified with a silane coupling agent. The thermosetting resin includes bisphenol epoxy resin, biphenyl epoxy resin and epoxy resin containing alicyclic skeleton.

2. The light-diffusing thermosetting sheet according to claim 1, wherein: The silicon dioxide particles are non-porous.

3. The light-diffusing thermosetting sheet according to claim 1, wherein: The content ratio of the surface-modified silica particles is 5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the thermosetting resin.

4. The light-diffusing thermosetting sheet according to claim 1, wherein: When the thermosetting resin composition is formed into a sheet having a thickness of 15 μm and thermally cured, the haze value is 35% or more and the total light transmittance is 80% or more.

5. The light-diffusing thermosetting sheet according to claim 1, wherein: The thermosetting resin composition further comprises pigment particles, The average primary particle size of the pigment particles is 100 nm or less.

Citation Information

Patent Citations

  • Image display device sealing material and image display device sealing sheet

    WO2018235824A1

  • Surface treatment silica particle, and manufacturing method of surface treatment silica particle

    JP2019189509A